The Effects of Neck Posture and Head Load on the Cervical Spine and Upper Extremities - Ibrahim, Ebram (My University, 2015)
Neck pain and injuries remain prevalent in many occupational categories. Risk factors include non-neutral neck postures and head loads. Most ergonomic tools do not account for the changes associated with these risk factors, or the effects that head position and load can have on the upper extremities. The purpose of this study was to investigate the effects of different neck postures and head loads on cervical discomfort and upper extremity functional integrity. Participants maintained flexed, extended, protracted, and neutral neck postures for a total of 4 minutes each. These trials were done both with and without a 3.68 kg head load. After each trial, measures of cervical discomfort, changes in hand sensation, hand and pinch grip strength, and holding forces were recorded. Cervical discomfort was found to increase in non-neutral postures and with the addition of a head load. Extension resulted in the greatest levels of discomfort, followed by flexion and protraction, with similar levels of discomfort, and neutral, which caused the least discomfort. Sternocleidomastoid activity increased in a loaded, non-neutral posture compared to an unloaded, neutral posture. These data could be implemented into current ergonomic tools to more comprehensively assess task demands and reduce the risk of injury.
Keywords: Neck; Cervical spine; Head load; Posture; Nerve impingement; Discomfort; Biomechanics; Ergonomics